BADUSH DAM: PLANNED AND DESIGNED AS A PROTECTION DAM, NW IRAQ - SISSAKIAN, VAROOJAN K.; ADAMO, NASRAT; AL-ANSAR, NADHIR (Journal of Duhok University, 2020)
Badush Dam is uncompleted combined earthfill and concrete dam, it is located on the Tigris River. The dam is planned and designed to be a protection dam downstream of the already existing Mosul Dam to protect population and infrastructure downstream of Mosul Dam. Thisa is attributed to the safety concerns of Mosul Dam which suffers from severe karstification in its foundation due to the presence of thick gypsum beds. The safety of Mosul Dam is a matter of debate since its construction and commissioning in 1986. The construction of Badush Dam started in 1988 and suspended in 1991, although (30 – 40) % of the dam was already built. The geological setting of Badush Dam is almost similar to that of Mosul Dam. Therefore, the foundation of Badush Dam will suffer from the same problem which is karstification because they are located on gypsum beds which are the same rocks under the foundations of Mosul Dam. The thin inclined clay core and foundation treatment works indicate clearly that Badush Dam is designed to have temporary nature which is to contain the volume of Mosul Dam wave (11 × 11 km3 ) in case of collapse of Mosul Dam and to pass the wave downstream without flooding.